Carbohydrate Restriction During Recovery from High-Intensity–Interval Training Enhances Fat Oxidation During Subsequent Exercise and Does Not Compromise Performance When Combined With Caffeine - Camilla Soegaard; Simon Riis; Jesper Friis Mortensen; Mette Hansen (Current Developments in Nutrition)
Background: Carbohydrate restriction can alter substrate utilization and potentially impair endurance performance in female athletes. Caffeine intake may mitigate this performance decrements. Objectives: The aim of this study was to test the hypothesis that maximal fat oxidation (MFO) rate would be enhanced in the carbohydrate (CHO) restricted state in trained females. Additionally, the impact of caffeine intake before exercise under conditions of low CHO availability was examined on time-trial performance. Methods: By using a randomized, double-blinded, placebo-controlled, crossover design, 17 female endurance athletes completed 3 experimental blocks. Each block consisted of high-intensity-interval–training (HIT) in the evening, followed by a fat oxidation test to measure MFO rate and a 20-min time trial (20TT) performance the next morning. The females received standardized, isoenergetic diets with different timing of CHO intake: No CHO between exercise sessions without (FASTED) or with 300 mg caffeine (4.1–4.9 mg/kg body mass) (FASTED+CAFF) before morning exercise tests or CHO ingestion after HIT (FED). Results: MFO rate was higher in FASTED+CAFF (0.57 ± 0.04 g/min) than that in FED (0.50 ± 0.04 g/min, P = 0.039) but not different from FASTED condition. Power output performed during the 20TT was higher after FASTED+CAFF (189 ± 9 W) than that after FASTED (+6.9%, P = 0.022) and FED (+4.2%, P = 0.054). Conclusions: CHO restriction during recovery from HIT enhances MFO rate during subsequent exercise compared with the condition where CHOs were consumed during the recovery period, but the effect was only significant when CHO restriction was combined with caffeine supplementation before the MFO test. In addition, caffeine ingestion before exercise in the CHO-restricted state compensates for the decreased work capacity associated with the CHO-restricted state.